IDENTIFIKASI FAUNA TANAH EPIGEON DAN HEMIEDAFON PADA SISTEM TUMPANGSARI TANAMAN JAGUNG (Zea mays L.) DAN KACANG TANAH (Arachis hypogaea L.) PADA PERLAKUAN MIKORIZA INDIGEN DAN PUPUK ORGANIK CAIR - Pakki, Terry; Halim, Halim; Arbiyanti, Arbiyanti (Jurnal Agroteknos, 2012)
This study aimed to determine the effect of indigenous mycorrhiza and liquid organic fertilizer on corn and peanut intercropping system and its effect on the epigeon and hemiedafon fauna population. This study was conducted by using three methods of sampling: pitfall trap, transect and funnel barlles. The result of this study showed that there were several types of epigeon and hemiedafon soil fauna to the corn and peanut intercropping system  that  treated  by  indigenous mycorhiza and  liquid  organic  fertilizer  :    they  were Cockroachest east (Blatta orientalis L.), Millipedes (Trigoniulus corallinus), Leech (Tyrnnobdella rex),  Black  fire  ants  (Selenopsis richteri),  Fire  ants  (Selenopsis geminata), Black ants (Dolichoderus bituberculatus), Centipede (Scolopendra sp.), Small red ants, Crickets  ground  (Allonemobius fasiatus),  Field  crickets  (Gryllus  pennsylvanicus), Ground spider (Lycosa sp.), German roaches (Blattella fasciatus), Termites (Coptotermes sp.), Snails (Achatina fulica) and Earthworm genus Lumbricus. The highest level of epigeon and hemiedafon soil fauna population was found at 4 MST; they were Black ants (Dolichoderus bituberculatus) and Termites (Coptotermes sp.) in one colony. The lowest level of epigeon and hemiedafon soil fauna population was found in untreated area (controlled). Key words :    soil  fauna,  epigeon,  hemiedafon,  intercropping  system,  indigen  mycorrhiza, liquid organic fertilizer